Komparasi Persepsi antar Stakeholder dalam Sinergi CSR dan Program Pembangunan Daerah - Rabin Ibnu Zainal (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2020)
In Indonesia, Corporate Social Responsibility (CSR) is an obligation of business companies at the area around the company's operations. The CSR mandate in the legislation makes the role of the company not only as a provider of goods and services in the economy, but also contributes as an alternative source of funds for development and public goods and services providers for the community, which is actually the duty of the government. In its implementation there will be many perceptions from each stakeholder both from the company, local communities, and the Regional Government where the company operates. This study uses a qualitative method by utilizing in-depth interviews with stakeholders related to corporate CSR, both from managers and staff of CSR management companies, local communities affected by the company and local government. Interviews were conducted to see the perceptions of each stakeholder in viewing the synergy of CSR programs and regional development, especially in the Musi Banyuasin district, South Sumatra. The results showed that there were differences in perceptions between each stakeholder towards other stakeholders in the implementation of CSR programs that originated from the interests of each stakeholder. The results of this study are expected to provide policy input on the integration of the company's CSR programs with the Development Program.